The ecological adaptation of the unparalleled plastome character evolution in slipper orchids - Hu, Chao; Jiao, Zhenbin; Deng, Xinyan; Tu, Xiongde; Lu, Aixian; Xie, Chengzhi; Jiang, Kai; Zeng, Xinhua; Liu, Zhong-Jian; Huang, Weichang; Luo, Yibo (Frontiers in Plant Science, 2022)
Plastomes may have undergone adaptive evolution in the process of plant adaptation to diverse environments, whereby species may differ in plastome characters. Cypripedioideae successfully colonized distinct environments and could be an ideal group for studying the interspecific variation and adaptive evolution of plastomes. Comparative study of plastomes, ancestral state reconstruction, phylogenetic-based analysis, ecological niche modelling, and selective pressure analysis were conducted to reveal the evolutionary patterns of plastomes in Cypripedioideae and their relationship with environmental factors. The plastomes of the three evolved genera had reduced plastome size, increased GC content, and compacted gene content compared to the basal group. Variations in plastome size and GC content are proved to have clear relationships with climate regions. Furthermore, ecological niche modelling revealed that temperature and water factors are important climatic factors contributing to the distributional difference which is directly correlated with the climate regions. The temperature-sensitive genes ndh genes, infA, and rpl20 were found to be either lost/pseudogenized or under positive selection in the evolved groups. Unparalleled plastome character variations were discovered in slipper orchids. Our study indicates that variations in plastome characters have adaptive consequences and that temperature and water factors are important climatic factors that affect plastome evolution. This research highlights the expectation that plants can facilitate adaptation to different environmental conditions with the changes in plastome and has added critical insight for understanding the process of plastome evolution in plants.